The Dynamics of Jember Sari Wedding Dress In Jember From 2005 To 2018 - Alifatul Inaayah; Sumarjono Sumarjono; Mohamad Na'im; Akhmad Ryan Pratama (JURNAL HISTORICA, 2021)
Jember Sari wedding dress is a original wedding dress of Jember regency. Jember Sari wedding dress consists of kebaya, beskap and jarit. The purpose of examining Jember Sari wedding dress is in order to mantain a regional wedding dress and preserve the existing culture. The result of the study is the apperarance motive of Jember Sari weding dress as follows; (1) Socio-cultural factors, due to the fusion process of Javanese and Madura culture. The Javanese and Madurese etnics coexisted in Jember, thereby the new culture is called â€œPandhalunganâ€ culture. One of the Pandalungan culture is the wedding dress of Jember Sari. (2) In 2003, HARPI "Melati" appealed to every region in order to obtain the regional wedding dress. After that, based on the idea of the HARPI "Melati" chairman Jember, then HARPI performed out the excamination and research towards Jember Sari wedding dress in 2005. Keywords: Wedding Dress, Jember Sari, Pandhalungan